1987
DOI: 10.1088/0022-3727/20/4/011
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental laws of anodic and cathodic arc duration on break at low electrical level

Abstract: This work deals with measurements of arc duration on break in electrical switching contacts in a resistive circuit I 2 A, and V < 50 V. A sensitive device was constructed with 10 ns time resolution and covering the arc time in the range 10 ns-l0 ms. For all contact materials tested (Ag, Cu, Pd, Au, Ag Pd, Ag Au, Ag Cu), experimental points of arc duration versus current are grouped around two theoretical curves corresponding respectively to anodic short arcs and cathodic long arcs. The analytical laws of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…For example, Suhara suggests, based on the experimental results of W contacts, that the conventional minimum arc current value should be considered as the load current value at which break arc discharges over 100 pts tend to occur with probability of 100% [5]. On the other hand, Ben Jemaa et al reported that arc discharges on the order of pts certainly occur at load current level of 0.2 to 0.3 A, and the conventional minimum arc current level will correspond to the transition boundary from anode arcs to cathode arcs [6][7]. The results presented in this paper support these such previous suggestions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Suhara suggests, based on the experimental results of W contacts, that the conventional minimum arc current value should be considered as the load current value at which break arc discharges over 100 pts tend to occur with probability of 100% [5]. On the other hand, Ben Jemaa et al reported that arc discharges on the order of pts certainly occur at load current level of 0.2 to 0.3 A, and the conventional minimum arc current level will correspond to the transition boundary from anode arcs to cathode arcs [6][7]. The results presented in this paper support these such previous suggestions.…”
Section: Discussionmentioning
confidence: 99%